Effects of laser radiation on surface tissues - Poh, Deh Tong. (2009)
Distribution of light in biological media has interested many researchers especially with the advancement in medical applications of laser. It is well known that light distribution in tissues is governed by the absorption coëfficiënt, jia, scattering coëfficiënt, fis and the anisotropy factor gr. Many researchers have already developed models to map the light distribution in tissues in order to understand its behaviour better.